فاعلية برنامج مقترح لتنمية المهارات البلاغية لطلاب الشهادة الدينية العالية الماليزية - عصام علي منصور الأشوح; نور عاشقين بنت عثمان; السيد محمد سالم (UIN Fatmawati Sukarno Bengkulu, 2023)
البحث استهدف البحث تنمية المهارات البلاغية لدى طلاب الشهادة الدينية العالية الماليزية الناطقين بغير العربية، عن طريق برنامج مقترح يقوم على طرائق تدريس حديثة لمادة البلاغة، وقد اختار الباحث كلية اللغة والدين السلطان أبو بكرـ بكان، بهانج؛ لتكون مجتمعا لبحثه، وتكونت عينة البحث من ( 112 ) طالبا، وتم تقسيم العينة إلى مجموعتين إحداهما تجريبية والأخرى ضابطة ؛ ولتحقيق أهداف البحث استخدم الباحث الأدوات الآتية:1. إعداد قائمة المهارات البلاغية اللازمة لطلاب الشهادة الدينية العالية الماليزية (STAM ).2. إعداد استبانة لمعرفة اتجاهات الطلاب نحو مادة البلاغة، وقياس المهارات البلاغية لديهم، ومعرفة أسباب ضعفهم في هذه المهارات من وجهة نظرهم.3. برنامج تنفيذي مقترح قائم على طرائق تدريس حديثة للبلاغة لتنمية المهارات البلاغية لدى طلاب (STAM ).4. اختبار تحصيلي لقياس المهارات البلاغية لدى طلاب (STAM[U1] ) بعد تطبيق البرنامج المقترح؛ لمعرفة مدى فاعلية هذا البرنامج.وقد أظهرت نتائج الدّراسة وجود فروق ذات دلالة إحصائيّة عند مستوى الدلالة (α= 0.05) بين المجموعتين ترجع إلى فاعلية البرنامج المقترح لصالح المجموعة التجريبية وفي ضوء نتائج البحث، أوصت الدراسة باعتماد البرنامج المقترح الذي يستند على طرائق تدريس حديثة للبلاغة.الكلمات المفتاحية: ( الفاعلية ـــــــــ البرنامج ـــــــــ المهارات البلاغية ــــــــ الشهادة الدينية العالية الماليزية). Abstract : The research aims to develop the rhetorical skills of students of the Malaysian high religious certificate who speak non-Arabic, through a proposed program based on modern teaching methods for rhetoric, The researcher chose the College of Language and Religion, Sultan Abu Bakr, Bekan, Pahang; To be a community for his research, and the research sample consisted of (112) students. To achieve the objectives of the research, the researcher used the following tools: 1. Preparing a list of rhetorical skills required for students of the Malaysian Higher Religious Certificate (STAM). 2. Preparing a questionnaire to find out students' attitudes towards rhetoric, measure their rhetorical skills, and find out the reasons for their weakness in these skills from their point of view. 3. A proposed executive program based on modern teaching methods for rhetoric to develop rhetorical skills among students (STAM). 4. An achievement test to measure the rhetorical skills of (STAM) students after applying the proposed program; To find out the effectiveness of this program. The results of the study showed that there were statistically significant differences at the significance level (α = 0.05) between, The two groups are due to the effectiveness of the proposed program in favor of the experimental group and in the light of the research results, the study was recommended, By adopting the proposed program, which is based on modern teaching methods of rhetoric.